Antibacterial Dental Composites with Chlorhexidine and Mesoporous Silica - Zhang, J.F. (J Dent Res, 2014)
One of the leading causes for the failure of dental composite restorations is secondary caries. Effectively inhibiting cariogenic biofilms and reducing secondary caries could extend the service life of composite restorations. Dental composites releasing antibacterial agents such as chlorhexidine (CHX) have shown biofilm-inhibitory efficacy, but they usually have poor physical and mechanical properties. Herein, we present a study of a new method to encapsulate and release CHX from dental composite using mesoporous silica nanoparticles (MSNs). SBA-15 MSNs were synthesized according to a reported procedure. CHX (62.9 wt%) was encapsulated into dried MSN from 0.3 M CHX ethanol solution. The dental composites containing 0% (control), 3%, 5%, and 6.3% CHX or the same amounts of CHX entrapped in MSN (denoted as CHX@MSN) were fabricated with methacrylate monomers and silanized glass fillers (CHX or CHX@MSN + glass filler particle = 70 wt%). The monomer mixture consisted of bisphenol A glycidyl methacrylate (BisGMA), hexanediol dimethacrylate (HDDMA), ethoxylated bisphenol A dimethacrylate (EBPADMA), and urethane dimethacrylates (UEDMA) at a weight ratio of 40:30:20:10. The composites were tested for CHX release and recharge, flexural strength and modulus (at 24 hr and 1 mo), surface roughness, in vitro wear, and antibacterial activity against Streptococcus mutans and Lactobacillus casei (in both planktonic growth and biofilm formation). The results showed that the composites with CHX@MSN largely retained mechanical properties and smooth surfaces and showed controlled release of CHX over a long time. In contrast, the composites with directly mixed CHX showed reduced mechanical properties, rough surfaces, and burst release of CHX in a short time. The composites with CHX either directly mixed or in MSN showed strong inhibition to S. mutans and L. casei. This research has demonstrated the successful application of MSNs as a novel nanotechnology in dental materials to inhibit oral biofilm without sacrificing materials’ mechanical properties and surface integrity.